Development of Semi-Instant Flour Mixes Product for Steamed Cassava Cake - Potasin, Wanlapa; Rongthong, Achiraya; Lapchuti, Charisa (Dusit Thani College Journal, 2023)
This research aims to develop of semi-instant flour mixes for steamed cassava cake. This study was conducted to study the optimum ratio of water content in instant flour mixes for making steamed cassava cake and analyze physical, chemical and microbial quality and study consumer acceptance. In this experiment, the amount of water added in the finished starch products was studied to 40 45 and 50%. It was found that the instant mixed starch formula for steamed cassava cake was based on the 50% water content for reconstitution, giving the highest acceptance scores on appearance, color, taste, aroma, texture, and overall acceptability when compared to use of water content of 40 and 45%, respectively. The average score in terms of taste, aroma, texture and overall liking was second only to standard steamed cassava cake. Which is equal to 7.10±1.20 7.06±1.24 7.06±1.33 and 7.12±1.14 respectively. The results of the study on the quality of steamed cassava cake using 50% water content for recovery, chemical quality, showed that moisture content, protein, fat, fiber, ash and carbohydrate content were 50.05±0.16 1.67±0.11 7.39±0.08 0.69±. 0.08, 0.91±0.06, and 39.30±0.34 respectively. The microbial quality total bacteria, yeast and mold were not exceed the standard of the Thai Community Product Standard, Thai dessert (MorChor. 1/2009).